Management Of Smart Tourism Implementation And Creative Economy Collaboration As A Strategy For Sustainable Tourism Development In Yogyakarta - L Tarigan, Nerys Lourensius; Larasati, Rian (JURNAL ILMU MANAJEMEN, 2025)
This study aims to analyse the role of smart tourism management and creative economy collaboration as strategies for sustainable tourism development in Yogyakarta. A quantitative method was used, involving 200 respondents consisting of tourism business operators, local communities, and tourists. Data was collected through questionnaires using a 1-5 Likert scale, then analysed using descriptive statistics and multiple linear regression to test the effect of the independent variables of smart tourism management and creative economy collaboration on the dependent variable of sustainable tourism. The results showed that the implementation of smart tourism, such as information technology, service digitalisation, and destination management systems, had a significant effect on tourism sustainability, while creative economy collaboration through local product development, community participation, and business innovation contributed more to supporting environmental preservation, improving the local economy, and strengthening cultural identity. These findings recommend the integration of technology-based policies and creative economic empowerment as key strategies for developing tourism in Yogyakarta, with a focus on improving human resource capacity and digital infrastructure. The implications of this research highlight the importance of multi-stakeholder collaboration to achieve holistic sustainability goals.